« Injure pour injure » : Une polémique presque invisible autour De la fréquente communion d’Antoine Arnauld - Yasushi Noro (Etudes Epistémè)
The scandal and controversy that surrounded the publication in August 1643 of Antoine Arnauld’s book De la fréquente communion are well known. Much ink was spilled in the 1640s by anti-Jansenists and Jansenists alike on this first book of Arnauld’s. This article, however, deals with another, much less known controversy, provoked by the same book but that became apparent only in several later editions. In order to respond to a preacher who had slandered him in the pulpit, Arnauld prepared a « Warning » as a preface for a later edition. The name of the preacher was Jacques Nouet (1605-1680), a Jesuit who continually attacked Arnauld’s book in his sermons, given in a Jesuit church in Paris. Although Nouet’s sermons are now lost, it is possible to reconstruct them in part, using the text of Arnauld’s « Warning » and other texts. Yet, what emerges above all is the impressive strategy that was carefully prepared by Arnauld and his supporters against the Jesuit’s attacks. This controversy, which remained nearly indiscernable in the first edition of De la Fréquente Communion, presents an interesting case of the battle of the pulpit against print.